Impact of ergot alkaloid and steroidal implant on whole-body protein turnover and expression of mTOR pathway proteins in muscle of cattle - Ferguson, Taylor D.; Loos, Caroline M. M.; Vanzant, Eric S.; Urschel, Kristine L.; Klotz, James L.; McLeod, Kyle R. (Frontiers in Veterinary Science, 2023)
Holstein steers (n=32) were used to determine if the ergot analog, bromocriptine decreases muscle protein synthesis through inhibitory action on the mTOR pathway via a direct effect on signal proteins, and if these negative effects can be alleviated with anabolic agents. Steers were treated with intramuscular administration of bromocriptine (vehicle or 0.1 mg/kg BW) and a subdermal commercial steroidal implant containing trenbolone acetate (TBA) and estradiol 17β (with or without), in a 2x2 factorial design. During the 35-day experiment, intake was restricted to 1.5 times maintenance energy requirement. On days 27 through 32, steers were moved to metabolism stalls for urine collection, and whole-body protein turnover was determined using a single pulse dose of [15N] glycine into the jugular vein on day 28. On day 35, skeletal muscle samples were collected before (basal state) and 60 mins after (stimulated state) an i.v. glucose challenge (0.25 g glucose/kg). Blood samples were collected at regular intervals before and after glucose infusion for determination of circulating concentrations of glucose and insulin. Bromocriptine reduced insulin and glucose clearance following the glucose challenge, indicating decreased insulin sensitivity and possible disruption of glucose uptake and metabolism in the skeletal muscle. Conversely, analysis of whole-body protein turnover demonstrated that bromocriptine does not appear to affect protein synthesis or urea excretion. Western immunoblot analysis of skeletal muscle showed that it did not affect abundance of S6K1 or 4E-BP1, so bromocriptine does not appear to inhibit activation of the mTOR pathway or protein synthesis. Estradiol/TBA implant decreased urea excretion and protein turnover but had no effect on protein synthesis, suggesting that steroidal implants promote protein accretion through unchanged rates of synthesis and decreased degradation, even in the presence of bromocriptine, resulting in improved daily gains. Implanted steers likely experienced increased IGF-1 signaling, but downstream activation of mTOR, S6K and 4E-BP1, and thus increased protein synthesis did not occur as expected. Overall, this data suggests that bromocriptine does not have a negative impact on muscle protein synthetic pathways independent of DMI.